The political construction of the left-right divide: a comparative perspective. Issue 3 (2nd September 2021) - Noël, Alain; Thérien, Jean-Philippe; Boucher, Émile
ABSTRACT: How universal and effective is the left-right opposition? We use public opinion data collected in 83 societies between 2008 and 2014 through the World Values Survey and the European Values Study, to look at the relationships, in each society, between individual ideological self-positioning and attitudes towards a set of eleven issues that capture the standard dimensions of the left-right political distinction. We observe varying levels of national ideological reach – the predictive power of left-right self-positioning on other attitudes – and ideological density – an index of the strength of the relationships between all the survey questions that we examine. These different levels of ideological reach and density can be explained by economic development, secularization, and democratic experience. A lasting experience with democracy, in particular, accounts best for the variations. When citizens have the capabilities and the possibilities of making political choices, they respond better to the elites' tendency to structure political debates in left-right terms.